Investment Banks as Corporate Monitors in the Early Twentieth Century United States - Frydman, Carola; Hilt, Eric (American Economic Review, 2017)
We study the effect of financial relationships on firms' investment decisions and access to external finance. In the early twentieth century, securities underwriters commonly held directorships with American corporations. Section 10 of the Clayton Antitrust Act prohibited bankers from serving on the boards of railroads for which they underwrote securities. We find that following the implementation of Section 10, railroads with strong preexisting relationships with underwriters saw declines in their investment rates, valuations, and leverage, and increases in their costs of external funds. Reassuringly, we do not observe similar effects among industrials and utilities, which were not subject to Section 10. Our results are consistent with underwriters on corporate boards acting as delegated monitors, and highlight the potential for regulations intended to address conflicts of interest to disrupt valuable information flows. (JEL G24, G31, G32, G34, K22, N21, N22)